2000
DOI: 10.1074/jbc.m909273199
|View full text |Cite
|
Sign up to set email alerts
|

12-O-Tetradecanoylphorbol-13-acetate (TPA)-induced c-Jun N-terminal Kinase (JNK) Phosphatase Renders Immortalized or Transformed Epithelial Cells Refractory to TPA-inducible JNK Activity

Abstract: Members of the mitogen-activated protein kinase (MAPK) 1 superfamily are proline-directed serine/threonine protein kinases that play pivotal roles in transducing various extracellular signals to the nucleus. They consist of three major subfamilies: MAPK/extracellular signal-regulated kinase (ERK), c-Jun N-terminal kinase (JNK)/stress-activated protein kinase (SAPK), and p38/Mpk2. MAPK/ERK is activated mainly by growth factors and phorbol esters and is associated with cellular proliferation and differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…Moreover, this induction of CYP4F11 was shown to be mediated by the JNK pathway as indicated by the loss of cytokine induction of CYP4F11, as well as c-Jun phosphorylation in the presence of JNK inhibitor SP600125. TPA had no effect on CYP4F11 mRNA levels in HaCaT, which is consistent with previous findings that TPA did not induce JNK activity in HaCaT cells (Zhou et al, 2000). CYP4F11 expression was strongly induced by addition of the cytokines TNF-␣ and IL-1␤ but not TPA, indicating the efficacy of AP-1 sites in regulation of CYP4F11 mRNA expression.…”
Section: Fig 4 Effects Ofsupporting
confidence: 80%
“…Moreover, this induction of CYP4F11 was shown to be mediated by the JNK pathway as indicated by the loss of cytokine induction of CYP4F11, as well as c-Jun phosphorylation in the presence of JNK inhibitor SP600125. TPA had no effect on CYP4F11 mRNA levels in HaCaT, which is consistent with previous findings that TPA did not induce JNK activity in HaCaT cells (Zhou et al, 2000). CYP4F11 expression was strongly induced by addition of the cytokines TNF-␣ and IL-1␤ but not TPA, indicating the efficacy of AP-1 sites in regulation of CYP4F11 mRNA expression.…”
Section: Fig 4 Effects Ofsupporting
confidence: 80%
“…We found that cisplatin, but not TPA was able to diminish the expression and activity of EGR-1 compared with 10% FCS. NF-κB and AP-1 play a critical role in the transcriptional regulation of genes that have been shown to suppress apoptosis and induce cellular transformation, proliferation, invasion, metastasis, chemo-resistance, radio-resistance and inf lammation (26,27,37,38). We also know that TPA is a potent stimulator of AP-1 trans-criptional activity and an efficient inducer of c-fos and c-jun gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…To address this possibility, cells were treated with CDDP in the presence of the phorbol ester TPA. Numerous studies have indicated that TPA is a strong activator of the ERK signaling pathway (7, 28 -30) at concentrations that do not alter JNK activities in HeLa cells (31,32). 2 Cells were pre-incubated with or without 50 nM TPA for 1 h, followed by addition of 20 M CDDP.…”
Section: Cddp Treatment Induces Apoptosis In Hela Cells-cddpmentioning
confidence: 99%